Effects of Night Shifts on Sleep, Cognitive Performance, and Anxiety in Emergency Nurses: An Observational Within‐Subject Study. - Casas-Méndez, Carlos; Martín-Parrilla, Miguel Ángel; Cáceres, Macarena C.; Montanero-Fernández, Jesús; López-Jurado, Casimiro Fermín; Durán-Gómez, Noelia; Carmona-Torres, Juan Manuel (Journal of Nursing Management, 2026)
Aims: To investigate the effects of night shifts (NS) on cerebral oxygenation, cognitive performance, and anxiety in emergency nurses and to examine the role of sleep duration in modulating these outcomes. Background: NS disrupt circadian rhythms, reduce sleep, and may impair prefrontal cortex function. Emergency nurses, who are exposed to high cognitive and emotional demands, are especially vulnerable to these disruptions, which may compromise psychological well‐being, occupational performance, and patient safety. Method: A prospective, observational, within‐subject, cross‐over study was conducted in 67 emergency nurses. Each participant was evaluated both after completing a NS and during a day shift following a full night of rest at home (NR), with the order of assessments randomly assigned and separated by a 14‐day washout period. Regional cerebral oxygenation (rSO2) and prefrontal cortex reactivity were measured using near‐infrared spectroscopy (NIRS) while performing a verbal fluency task. Cognitive performance, sleep disturbance, and state anxiety were assessed with validated instruments: State Trait Anxiety Inventory (STAI), Insomnia Severity Index, and NIRS with Verbal Fluency Test (VFT). Results: After NS, nurses showed a significant decline in rSO2 (67.65 ± 6.37 vs. 64.45 ± 6.78; p < 0.001), reduced performance in the VFT (47.19 ± 11.14 vs. 42.85 ± 11.99; p < 0.001), and increased state anxiety (14.63 ± 9.53 vs. 21.37 ± 7.67; p < 0.001). Shorter sleep duration during NS was associated with lower rSO2 mean in both conditions: NR and NS. Interestingly, nurses who reported longer sleep during NS exhibited higher rSO2 but paradoxically poorer cognitive performance, suggesting that those with shorter sleep may have engaged compensatory mechanisms in those with shorter sleep that allowed them to maintain task performance despite reduced rSO2. Conclusions: Reduced sleep during NS negatively affected cerebral oxygenation, cognitive performance, and emotional well‐being in emergency nurses. Longer self‐reported sleep did not necessarily confer cognitive benefits and may reflect inefficient or overestimated sleep. Implications for Nursing Management: Organizational strategies are needed to mitigate the adverse effects of NS work. Optimizing shift schedules, ensuring structured rest opportunities, and implementing programs aimed at reducing anxiety and supporting psychological well‐being could help protect nurses' health, sustain performance, and improve patient safety.